2014
DOI: 10.1130/l340.1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of passive-roof duplexes in the Colombian Subandes and Perú

Abstract: Passive-roof duplexes are important features for accommodating shortening in active orogens, but their occurrences have been previously demonstrated only with significant subsurface data or after their exhumation. In this study, we describe a series of thin-skinned passive-roof duplexes along the Subandean front in Colombia and compare them with potential analogues in southern Peru. We suggest type localities for this structural style, which display conditions favorable for formation of these structures. It ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Abundant evidence shows that crustal shortening on the flanks of the Eastern Cordillera has occurred [e.g., Bayona et al, 2008;Cediel et al, 2003;Colletta et al, 1990;Cortés et al, 2006;Dengo and Covey, 1993;Egbue and Kellogg, 2012;Mora et al, 2008Mora et al, , 2010aMora et al, , 2010bMora et al, , 2010cMora et al, , 2014 and that therefore the high terrain is, at least in part, the result of crustal thickening and isostatic balance. This crustal shortening has been built, at least in part, on structures that initially developed during a Mesozoic stage of crustal extension when grabens and normal faults formed [e.g., Cediel et al, 2003;Jimenez et al, 2013;Moreno et al, 2013;Roeder and Chamberlain, 1995;Roure et al, 1997;Sarmiento-Rojas et al, 2006;Tesón et al, 2013].…”
Section: Geological and Seismological Constraints On The Deep Structumentioning
confidence: 99%
See 2 more Smart Citations
“…Abundant evidence shows that crustal shortening on the flanks of the Eastern Cordillera has occurred [e.g., Bayona et al, 2008;Cediel et al, 2003;Colletta et al, 1990;Cortés et al, 2006;Dengo and Covey, 1993;Egbue and Kellogg, 2012;Mora et al, 2008Mora et al, , 2010aMora et al, , 2010bMora et al, , 2010cMora et al, , 2014 and that therefore the high terrain is, at least in part, the result of crustal thickening and isostatic balance. This crustal shortening has been built, at least in part, on structures that initially developed during a Mesozoic stage of crustal extension when grabens and normal faults formed [e.g., Cediel et al, 2003;Jimenez et al, 2013;Moreno et al, 2013;Roeder and Chamberlain, 1995;Roure et al, 1997;Sarmiento-Rojas et al, 2006;Tesón et al, 2013].…”
Section: Geological and Seismological Constraints On The Deep Structumentioning
confidence: 99%
“…Most, however, suggest that crustal shortening responsible for the Eastern Cordillera began earlier. Some have concluded that initiation of important shortening began in Middle Miocene time [e.g., Bayona et al, 2008;Colletta et al, 1990;Cooper et al, 1995;Dengo and Covey, 1993;Gómez et al, 2005b;Hoorn, 1993;Hoorn et al, 1995;Mora et al, 2014], but a consensus suggests that a nonnegligible amount of shortening occurred earlier in Cenozoic time [e.g., Babault et al, 2013;Bande et al, 2012;Bayona et al, 2013;Caballero et al, 2013;Campos and Mann, 2015;Cediel et al, 2003;Egbue and Kellogg, 2012;Gómez et al, 2003;Hoorn et al, 2010;Horton et al, 2010;Martinez, 2006;Mora et al, 2010bMora et al, , 2010cOchoa et al, 2012;Parra et al, 2009aParra et al, , 2009bParra et al, , 2012Sánchez et al, 2012;Saylor et al, 2011Saylor et al, , 2012Villamil, 1999]. GPS velocities can be used to test whether crustal thickening in 3-6 Myr could build the Eastern Cordillera, or a longer duration is needed.…”
Section: Geological and Seismological Constraints On The Deep Structumentioning
confidence: 99%
See 1 more Smart Citation
“…) are considered here, in the Eastern Cordillera and the Middle Magdalena Valley (MMV). The Eastern Cordillera features complex structure, including imbricate and out‐of‐sequence thrusting, passive‐roof duplexes and anastomosing faults (Mora et al ., , ), rendering interpretation of burial and exhumation histories challenging, while the Middle Magdalena Valley is the site of rapid burial beginning in the Eocene and accelerating in the Mio‐Pliocene (Parra et al ., ).…”
Section: Case Studiesmentioning
confidence: 99%
“…Physical experiments predict that passive roof duplexes are more common in zones of efficient surface erosion (Mora et al, 2014, and references therein), consistent with critical taper wedge mechanics of thin-skinned thrust belts (e.g., Davis et al, 1983). Since their first recognition, it has been postulated that efficient sediment storage in the adjacent monocline along the deformation front is critical to the formation of passive roof duplexes (Mora et al, 2014). In the Lazi region, evidence that might support the existence of a passive roof duplex includes: (1) the presence of imbricate, foreland-dipping (south-dipping) thrust sheets, (2) the absence of an emergent, hinterland-dipping fault, (3) early Miocene syntectonic sedimentation in a contractional setting in the upper Kailas Formation and the Liuqu Formation and (4) growth structures in the Liuqu Formation ( Fig.…”
Section: Structural Modelmentioning
confidence: 85%